‘Stuck in place?’ A place-based study of how far education contributes to social mobility for working-class women in a former coalmining town. - Wright, Brittany (2024)
If upward social mobility involves moving from one social position to a higher one, social immobility should involve staying still. Yet this thesis demonstrates that all social agents travel in social space, regardless of whether their trajectories are classed as mobile or immobile. Whilst policymakers see schools as sites of social mobility, the findings presented here suggest that education is just one field that social agents travel through, patterned with the inequalities that pervade other social fields and the overarching field of power. Place is the prism through which these social inequalities are refracted: the locus for a social agent’s positions in overlapping social fields. By synthesising Pierre Bourdieu’s theoretical-methodological toolkit with Doreen Massey’s conception of space as relational, interconnected, and characterised by multiplicity, this place-based study maps the educational inequalities faced by working-class girls and women who have lived, learned, and worked in Coalville from the mid-20th century to the 21st century. Through historical ethnography, the study illustrates how inequalities are (re)produced over time. Schooling opens up or closes down opportunities for working-class women based on their positions within complex webs of social relations. Far from being engines of social mobility, the capacity of schools to promote upward mobility can be constrained by their own positions within social space and place.